2007
DOI: 10.1063/1.2764212
|View full text |Cite
|
Sign up to set email alerts
|

Growth and characterization of InAs columnar quantum dots on GaAs substrate

Abstract: The growth of InAs columnar quantum dots (CQDs) on GaAs substrates by molecular beam epitaxy was investigated. The CQDs were formed by depositing a 1.8 monolayer (ML) InAs seed dot layer and a short period GaAs/InAs superlattice (SL). It was found that the growth of the CQDs is very sensitive to growth interruption (GI) and growth temperature. Both longer GI and higher growth temperature impact the size dispersion of the CQDs, which causes the broadening of photoluminescence (PL) spectrum and the presence of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
60
0

Year Published

2007
2007
2008
2008

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 31 publications
(62 citation statements)
references
References 40 publications
2
60
0
Order By: Relevance
“…Due to their flat shape and quasibiaxial compressive strain, self-assembled quantum dots have a valence-band ground state of the heavyhole ͑hh͒ type, which does not couple to light polarized along the growth axis, i.e., transverse-magnetic ͑TM͒ mode in a guided-wave configuration. A hope exists, however, that both the shape of the confinement potential and the strain distribution can be changed by varying the QD aspect ratio, e.g., by changing the QD growth conditions, [4][5][6] or using a capping layer, 7 or close-stacking of several QDs. 8 In particular, depositing a short-period GaAs/ InAs superlattice ͑SL͒ on top of a seed QD layer results in the formation of columnar quantum dots ͑CQDs͒ with high aspect ratio.…”
Section: Polarization Dependence Study Of Electroluminescence and Absmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to their flat shape and quasibiaxial compressive strain, self-assembled quantum dots have a valence-band ground state of the heavyhole ͑hh͒ type, which does not couple to light polarized along the growth axis, i.e., transverse-magnetic ͑TM͒ mode in a guided-wave configuration. A hope exists, however, that both the shape of the confinement potential and the strain distribution can be changed by varying the QD aspect ratio, e.g., by changing the QD growth conditions, [4][5][6] or using a capping layer, 7 or close-stacking of several QDs. 8 In particular, depositing a short-period GaAs/ InAs superlattice ͑SL͒ on top of a seed QD layer results in the formation of columnar quantum dots ͑CQDs͒ with high aspect ratio.…”
Section: Polarization Dependence Study Of Electroluminescence and Absmentioning
confidence: 99%
“…8 In particular, depositing a short-period GaAs/ InAs superlattice ͑SL͒ on top of a seed QD layer results in the formation of columnar quantum dots ͑CQDs͒ with high aspect ratio. [4][5][6][9][10][11] The polarization properties of photoluminescence ͑PL͒ from the cleaved edge have been investigated for CQDs ͑Refs. 4, 12, and 13͒ and evidence of net TM gain under optical pumping has been reported very recently, 12 but no lasing.…”
Section: Polarization Dependence Study Of Electroluminescence and Absmentioning
confidence: 99%
“…The plane-view images revealed that they have a diamond ͑rhombus͒ shape with diagonals along the ͓110͔ and ͓1-10͔ directions and their length ratio is typically 1.22. 5 The cross-sectional TEM images ͑see Fig. 1͒ show they have the aspect ratio larger than 4 ͑height of 41 nm and the diagonal length of 10 nm, approximately͒ and an almost constant In content in the quantum rod ͑ϳ40% ͒ and in the surrounding two-dimensional ͑2D͒ "immersion" layer ͑ϳ15% ͒.…”
mentioning
confidence: 99%
“…In this case, the preferential incorporation of In adatoms in strained areas on top of the seed QDs leads to the formation of "column-shaped" nanostructures. Recently, this technique was extended to demonstrate InGaAs QDs with an aspect ratio exceeding 1, [3][4][5][6] leading to the formation of vertical quantum rods, also called "quantum posts." Additionally, it was shown that the In content profile in the vertical direction can be controlled by varying the deposition duty cycle.…”
mentioning
confidence: 99%
See 1 more Smart Citation